Desert star - Connelly, Michael, 1956- (2022)
"A year has passed since LAPD detective Renée Ballard quit the force in the face of misogyny, demoralization, and endless red tape. Yet, after the chief of police himself tells her she can write her ticket within the department, Ballard takes back her badge, leaving "the Late Show" to rebuild the cold case unit at the elite Robbery-Homicide Division. For years, Harry Bosch has been working a case that haunts him but that he hasn't been able to crack-the murder of an entire family by a psychopath who still walks free. Ballard makes Bosch an offer: come work with her as a volunteer investigator in the new Open-Unsolved Unit, and he can pursue his "white whale" with the resources of the LAPD behind him"--